¿Desarrollo comunitario? No lo sé, dímelo tú... (interrogantes desde una «iniciativa barrial») - Ramos, Alfredo; Casadevante, José Luis F.; Haro, José; Murgui, Ignacio (Cuadernos de Trabajo Social, 2006)
With this article, we seek to make a debate possible about our community experience in the Retiro district (Madrid). It is an experience which is too stubborn to adapt itself to various users’ manuals. We outline here our unique qualities and enunciate what we have been doing, with the hope that suggestions can be made with this sketch. We also refer to the breaks along the way which make up our story, which can be understand as questions that can be lifted from the text.